A Comparative Analysis of Subsidy Reforms in the Middle East and North Africa Region - Araar, Abdelkrim (World Bank, Washington, DC, 2016)
The paper compares the distribution of energy and food subsidies across households and the impact of subsidy reforms on household welfare in the Middle East and North Africa region. The analysis uses a unified model and harmonized household data. The results show that the distribution of subsidies and the welfare effects of subsidy reforms are quite diverse across countries and products. Energy subsidies tend to be pro-rich in terms of absolute amounts, but tend to be more important for the poor in terms of expenditure shares. Instead, food subsidies are larger for the poor in absolute and relative terms. These findings do not apply everywhere, and the scale of these phenomena are different across countries and products. The welfare effect of a 30 percent reduction in subsidies can be important, especially considering the cumulated effect across products, but the cost of compensating the loss in welfare for the poor is generally low compared with the budget benefits of decreasing subsidies.